Parents’ Experiences after Their Child’s Autism Diagnosis: A Reflexive Thematic Analysis - Robert Hughes; Kenneth Curley; Yasuhiro Kotera (Psychiatry International)
A child’s autism diagnosis is life-changing for their parents, due to the complex and long-term nature of the condition. Furthermore, research about the increased prevalence of autism suggests that more parents are being affected globally. However, limited studies have investigated parents’ lived experience of their child being diagnosed with autism. This study aimed to explore the first-hand experience and concerns of parents when their child has been diagnosed with autism. The study employed a qualitative, exploratory design. Parents of a child who had received an autism diagnosis at least 12 months prior were invited to a video interview. Eleven parents participated in an hour-long interview. The interviews were transcribed, and an inductive reflexive thematic analysis was performed. The analysis resulted in four main themes: “Shock and control”, “A thousand little conversations”, “Put your own oxygen mask on first”, and “Reforged identities”, orientating around the period surrounding diagnosis, ongoing communication requirements, the need for self-care and reorientation of identity. These findings identify areas of heightened concern for parents and provide professionals with practical insight when evaluating their engagement approaches with these groups of parents. Findings can help psychologists, therapists, educators and parents themselves to identify strategies to support the well-being of parents who have an autistic child.